2008
DOI: 10.1177/1367493507085615
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the views of parents of children with special needs about the nursing care their child receives when in hospital: a qualitative study

Abstract: This article reports a qualitative study designed to explore parents' views on how their child with additional needs had been cared for by hospital nursing staff, focusing on how well their own and their child's needs had been identified and met. Twelve interviews with parents of children with additional needs and a thematic analysis of the interview data was conducted. Four themes were developed to provide an insight into parents' views about their experiences: their prior experiences of hospital care, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 19 publications
10
72
0
7
Order By: Relevance
“…Although negotiation is a high priority for some nurses (Young et al 2006), parents still reported that barriers between nurses and parents are not addressed (Roden 2005, Coyne and Cowley 2007, Coyne 2008, Avis and Reardon 2008. However, nurses who were interviewed in the study by Young et al (2006) cared for children with acute medical needs, whereas Avis and Reardon (2008) interviewed the parents of children with special needs. Those who cared for the latter group of children may have assumed that the parents were more competent to provide care for them, and that negotiation was unnecessary.…”
Section: Emerging Themesmentioning
confidence: 89%
See 3 more Smart Citations
“…Although negotiation is a high priority for some nurses (Young et al 2006), parents still reported that barriers between nurses and parents are not addressed (Roden 2005, Coyne and Cowley 2007, Coyne 2008, Avis and Reardon 2008. However, nurses who were interviewed in the study by Young et al (2006) cared for children with acute medical needs, whereas Avis and Reardon (2008) interviewed the parents of children with special needs. Those who cared for the latter group of children may have assumed that the parents were more competent to provide care for them, and that negotiation was unnecessary.…”
Section: Emerging Themesmentioning
confidence: 89%
“…In these respects their expectations appear to be aligned with those of nurses (Paliadelis et al 2005, Roden 2005, Lam et al 2006, Coyne and Cowley 2007, Avis and Reardon 2008, Sousa et al 2013. Indeed, 97% of the parents who were interviewed in a study by Sousa et al (2013) said that if they were staying overnight with their children, they should participate fully in their care throughout the night, alongside the nurses.…”
Section: Emerging Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for good communication that prepares parents or legal guardians for the eventuality that their child might or will die has been identified as an important factor in coping with the situation (Avis & Reardon, 2008;Coad et al, 2014;Midson & Carter, 2010). The importance of good communication within families has also been highlighted as a significant factor in how well they cope with a life-threatened or life-limited child (Coad et al, 2014).…”
Section: Children Young People and Family Perspectivesmentioning
confidence: 99%